Advances in Neuroprotective Ingredients of Medicinal Herbs by Using Cellular and Animal Models of Parkinson's Disease. (1st September 2013) - More, Sandeep Vasant; Kumar, Hemant; Kang, Seong Mook; Song, Soo-Yeol; Lee, Kippeum; Choi, Dong-Kug
Abstract : Parkinson's disease (PD) is a multifactorial disorder, which is neuropathologically identified by age-dependent neurodegeneration of dopaminergic neurons in the substantia nigra. Development of symptomatic treatments has been partly successful for PD research, but there remain a number of inadequacies in therapeutic strategies for the disease. The pathogenesis of PD remains intricate, and the present anti-PD treatments appears to be clinically insufficient. Comprehensive research on discovery of novel drug candidates has demonstrated that natural products, such as medicinal herbs, plant extracts, and their secondary metabolites, have great potential as therapeutics with neuroprotective activity in PD. Recent preclinical studies suggest that a number of herbal medicines and their bioactive ingredients can be developed into optimum pharmaceuticals for treating PD. In many countries, traditional herbal medicines are used to prevent or treat neurodegenerative disorders, and some have been developed as nutraceuticals or functional foods. Here we focus on recent advances of the evidence-linked neuroprotective activity of bioactive ingredients of herbal origin in cellular and animal models of PD research.